The impact of ageing population on the social security budget: Case study for Brazil, China, Germany, Japan, and the United States - Roşca Vlad; Rădoi Mădălina (Budgetary Research Review (BRR), 2012)
This study estimates the hypothetical level of contributions collected and pensions paid in the future by the social security budget in five of the most influential countries in the world today. Historical data from 1980 to 2009 declared by each state's monitoring organization have been analyzed in order to find and propose a forecasting model for the period 2010-2025. Two models have been developed based on global specialists' data for complex forecasts on population changes and economic prospects: one both measuring and forecasting the contributions gathered for the social security budgets, and one forecasting the levels of pensions paid. The focus of the analysis is on the effects that an ageing population could have on social security budget. The models suggest that there is a real need for change in the social security systems in use in order to strategically avoid predictable deficits and achieve budgetary equilibrium.
Keywords: H55; 330; ageing population; social security